The Internet addiction among students of primary schools and lower and upper secondary schools and its relation to their level of physical activity - Katarzyna Zuń; Magdalena Zych; Marcin Stanisław Rząca; Katarzyna Kocka (Journal of Education, Health and Sport, 2017)
Introduction: Physical activity is an important part of a healthy lifestyle, which significantly affects the development of children and youth. Unfortunately, students take less and less physical activity devoting much more time to surfing the Internet.